The Views of The Women Activists in Sri Lanka on The Validity of Walī in A Marriage: A Juristic Analysis - Mohamed Buhary Fowzul (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
Abstract The women activists in Sri Lanka, namely the Muslim Women Research and Action Forum (MWRAF) advocate for reform in the Muslim Marriage and Divorce Act of Sri Lanka (MMDA). Nonetheless, since the Shāfiʿī Madhhab is predominant in Sri Lanka, the All-Ceylon Jam-e-athul Ulama (ACJU) - the mainstream organization of the jurists in Sri Lanka refutes the demands of the MWRAF. Consequently, there has been a deadlock over the years between the MWRAF and the ACJU. Hence, this research aims to analyse the critiques of the MWRAF regarding the validity of Walī (legal guardian) in a marriage and the responses of the ACJU. Accordingly, it explores the arguments of the women activists and their justifications such as the prioritisation of the opinions of the Ḥanafī jurists, refusal of the Ḥadīths regarding the Walī and the claim that the Ḥadīths regarding the Walī are contradictory to the Qur’an. Moreover, it analyses the coercion of matured and unmatured bride. Since this is a juristic analysis, it draws on the Quran, the Ḥadīths and the opinions of the classical and the modern jurists. Finally, this research finds that the critiques of the women activists are against the majority opinion of the jurists and proves that validating the marriage without Walī cause detrimental effects in the Muslim Community of Sri Lanka. Hence, this research enlightens the women activists regarding validity of Walī in a marriage providing the persuasive evidence from the divine texts and the prominent jurists. Keywords: Islamic Jurisprudence, Marriage, Sri Lanka, Walī, Women Activists